A.02 Assessing visual functions in children with an optic pathway glioma using steady-state visual evoked potentials. (2nd June 2017) - Zakaib Rassi, S; Ospina, L; Samson, Y; Saint-Amour, D; Perreault, S
Abstract : Background: Optic pathway gliomas (OPG) represent 5% of pediatric brain tumours. Visual acuity measures are used to evaluate treatment response. Current clinical tests to assess visual field integrity are subjective and require verbal cooperation. Thus, the objective of this study was to evaluate the clinical effectiveness of Steady State Visual Evoked Potentials (ssVEPs) to measure visual field integrity in a non-invasive and objective manner.Methods: SsVEPs were obtained in ten children with OPGs and 42 controls ages 3 to 21. The stimuli consisted of two circular dartboard patterns stimulating fovea and peripheral zones at two flickering frequencies, so that central and peripheral visual fields could be assessed simultaneously. The test consisted of eight stimuli presentations of 10 seconds.Results: Results indicate significantly lower ssVEP amplitudes in children with OPGs ( M =2.52, 95% CI [1.13, 3.92]) compared to controls ( M =13.26, 95% CI [8.85, 17.67]) in the central visual field ( p =.021). However, no between group differences were detected in the peripheral field ( p >.05). There were no significant differences between age groups (p>0.05).Conclusions: This objective, affordable, and non-invasive method appears to be effective in detecting central visual field deficits in children with OPGs rapidly and consistently.